2017
DOI: 10.12991/mpj.2017.7
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic and anti-inflammatory activity of crude leaf and bark extract of Lantana Camara

Abstract: The purpose of present study was to investigate the analgesic and anti-inflammatory activity of Lantana camara (Verbenaceae) leaf and bark extract. The methanol extract of Lantana camara (MELC) was screened for possible analgesic activity by acetic acid, hot plate and anti-inflammatory activity by carrageenan and histamine induced paw edema. The result showed that, MELC (100 mg/kg and 200 mg/kg) leaf and bark possessed significant (P <0.01 and P <0.05) anti-inflammatory response and 200 mg/kg dose of MELC leaf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…However, it is also possible that some other compounds interact synergistically or antagonistically. The anti-inflammatory activity of L. camara extracts has previously been demonstrated in several studies [12,[74][75][76]. However, IC 50 values were lower than 17.75 µg/mL in the present study (IC 50 of L. camara essential oil from Peru was 81.5 µg/mL [7]), indicating that L. camara is a plant with anti-inflammatory properties in various forms, supporting the wide use of this plant in traditional medicine for its anti-rheumatism properties [5].…”
Section: Evaluation Of Essential Oil Anti-inflammatory Activitymentioning
confidence: 74%
See 1 more Smart Citation
“…However, it is also possible that some other compounds interact synergistically or antagonistically. The anti-inflammatory activity of L. camara extracts has previously been demonstrated in several studies [12,[74][75][76]. However, IC 50 values were lower than 17.75 µg/mL in the present study (IC 50 of L. camara essential oil from Peru was 81.5 µg/mL [7]), indicating that L. camara is a plant with anti-inflammatory properties in various forms, supporting the wide use of this plant in traditional medicine for its anti-rheumatism properties [5].…”
Section: Evaluation Of Essential Oil Anti-inflammatory Activitymentioning
confidence: 74%
“…Different solvent extracts produced from L. camara have already been studied, showing the occurrence of flavonoids, triterpenes, and glycosides [5]. These extracts and compounds were described as having interesting antioxidant, anti-inflammatory [11][12][13], antibacterial, cytotoxic, antifungal, anthelmintic [14][15][16][17][18], and insecticidal properties [19,20]. Some studies have also focused on L. camara essential oils, showing the high diversity in essential oil compositions depending on plant growth area.…”
Section: Introductionmentioning
confidence: 99%
“…It is well established that medicinal plants are consistently explored for their therapeutic potentials from ages. Preclinical and clinical studies on various medicinal plants and their phytoconstituents have reported for exhibiting potential anti-inflammatory activities in the management of complex conditions like psoriasis and cancer [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Methanolic extracts of the leaves and bark of lantana extract at a dose of 2000 mg/kg orally, do not exhibit any signs of toxicity in rats up to 14 days and no animal died [85].…”
Section: Side Effects and Toxicitymentioning
confidence: 95%
“…Methanolic extracts of the leaves and bark of lantana extract were screened for analgesic activity by acetic acid and hot plate, and antiinflammatory activity by carrageenan and histamine-induced paw edema models. Methanolic leaf and bark extracts (100 and 200 mg kg body weight BW) possessed significant anti-inflammatory effects, and at 200 mg/kg dose, the extracts showed significant analgesic activity [85].…”
Section: Anti-inflammatory and Analgesic Effectsmentioning
confidence: 99%